Tinjauan Komprehensif: Simulasi Sistem Disk Scheduling dengan Berbagai Algoritma Menggunakan OS Sim - Putri, Fidel Lusiana; Djuniadi; Rochim, Febry Putra (ELECTRON Jurnal Ilmiah Teknik Elektro, 2025)
Disk scheduling is one of the important components in operating system resource management to optimize data access on storage devices. Operating systems use various algorithms to manage input/output (I/O) requests more efficiently, including Shortest Seek Time First (SSTF), LOOK, and Circular LOOK (C-LOOK). This research aims to evaluate and compare the performance of these algorithms in managing disk requests through simulations using OS-SIM. The applied methodology includes simulating a queue of random I/O requests on disks with specific configurations. The data analyzed includes Total Head Movement (THM) and Average Seek Time (AST) for each algorithm. The simulation is performed with a predefined initial position of the disk head, and each algorithm is tested based on how each of them manages the disk access sequence. The results show that the SSTF algorithm is the most efficient with the lowest THM and AST values of 208 tracks and 29.71 ms AST, compared to the LOOK and C-LOOK algorithms. The LOOK algorithm provides a balance between efficiency and fairness, as it is able to minimize head movement without ignoring distant requests. Meanwhile, C-LOOK is more effective in reducing the possibility of starvation on requests at the end of the disk, but at the cost of increasing the number of head movements. This research provides a clearer picture of the advantages and disadvantages of each algorithm, which can be used as a reference in the selection of disk scheduling algorithms in systems that require high efficiency and reliability in I/O management.